2015
DOI: 10.1097/hp.0000000000000285
|View full text |Cite
|
Sign up to set email alerts
|

Radon and Thoron Measured in Petrol and Gas-oil Exhaust Fumes by Using CR‐39 and LR‐115 II Nuclear Track Detectors

Abstract: Mechanic workers are exposed to exhaust fumes when controlling vehicle engines in motion inside repair shops. To assess radiation doses due to radon short-lived progeny from the inhalation of exhaust fumes by mechanic workers, concentrations of these radionuclides were measured in petrol (gasoline) and gas-oil exhaust fumes by evaluating mean critical angles of etching of the CR-39 and LR-115 type II SSNTDs for alpha particles emitted by the radon and thoron decay series. Committed effective doses due to ²¹⁸Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Alpha-particles emitted by both attached and unattached fractions of 222 Rn and 220 Rn progeny can cause damage to tissues of the respiratory system (Misdaq et al 1997). 222 Rn, 220 Rn, and their progeny are present in the air of dwellings and workplaces (Dehnert et al 2020;Sharma et al 2018;Singh et al 2015;ICRP 1993;Prasad et al 2016;Yu et al 1997;Ha et al 1999;UNSCEAR 1993;Misdaq et al 2015a). According to previous works, it has been shown that concentration levels of 222 Rn, 220 Rn and their progeny are significantly increased when pollutants are present in indoor air such as cigarette smoke (Misdaq and Flata 2003), thermal water vapor (Nikolopoulos et al, 2010;Silva and Dinis 2017;Misdaq et al 2012), marble dusts (Misdaq et al 2019), and petrol and gas-oil exhaust fumes (Misdaq et al 2015a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Alpha-particles emitted by both attached and unattached fractions of 222 Rn and 220 Rn progeny can cause damage to tissues of the respiratory system (Misdaq et al 1997). 222 Rn, 220 Rn, and their progeny are present in the air of dwellings and workplaces (Dehnert et al 2020;Sharma et al 2018;Singh et al 2015;ICRP 1993;Prasad et al 2016;Yu et al 1997;Ha et al 1999;UNSCEAR 1993;Misdaq et al 2015a). According to previous works, it has been shown that concentration levels of 222 Rn, 220 Rn and their progeny are significantly increased when pollutants are present in indoor air such as cigarette smoke (Misdaq and Flata 2003), thermal water vapor (Nikolopoulos et al, 2010;Silva and Dinis 2017;Misdaq et al 2012), marble dusts (Misdaq et al 2019), and petrol and gas-oil exhaust fumes (Misdaq et al 2015a).…”
mentioning
confidence: 99%
“…222 Rn, 220 Rn, and their progeny are present in the air of dwellings and workplaces (Dehnert et al 2020;Sharma et al 2018;Singh et al 2015;ICRP 1993;Prasad et al 2016;Yu et al 1997;Ha et al 1999;UNSCEAR 1993;Misdaq et al 2015a). According to previous works, it has been shown that concentration levels of 222 Rn, 220 Rn and their progeny are significantly increased when pollutants are present in indoor air such as cigarette smoke (Misdaq and Flata 2003), thermal water vapor (Nikolopoulos et al, 2010;Silva and Dinis 2017;Misdaq et al 2012), marble dusts (Misdaq et al 2019), and petrol and gas-oil exhaust fumes (Misdaq et al 2015a). To assess radiation exposure for workers inside spa rooms, one should measure concentrations of 222 Rn,220 Rn, and their progeny in the air of these rooms.…”
mentioning
confidence: 99%